2019
DOI: 10.1038/s41598-018-37614-3
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation reveals multi-stage coding of visual duration

Abstract: In conflict with historically dominant models of time perception, recent evidence suggests that the encoding of our environment’s temporal properties may not require a separate class of neurons whose raison d'être is the dedicated processing of temporal information. If true, it follows that temporal processing should be imbued with the known selectivity found within non-temporal neurons. In the current study, we tested this hypothesis for the processing of a poorly understood stimulus parameter: visual event d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 75 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…The neurobehavioral correlation is also relevant to the current debate concerning where our subjective experience of time arises from within the temporal processing hierarchy ( Shima et al, 2016 ; Li et al, 2017a ; Heron et al, 2019 ). Some researchers have proposed that duration channels are located in early processing stages given psychophysical evidence showing that duration aftereffects exhibit modality ( Heron et al, 2012 ; Li et al, 2019 ) and, with visual stimuli, some degree of spatial specificity ( Fulcher et al, 2016 ; see also Johnston et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The neurobehavioral correlation is also relevant to the current debate concerning where our subjective experience of time arises from within the temporal processing hierarchy ( Shima et al, 2016 ; Li et al, 2017a ; Heron et al, 2019 ). Some researchers have proposed that duration channels are located in early processing stages given psychophysical evidence showing that duration aftereffects exhibit modality ( Heron et al, 2012 ; Li et al, 2019 ) and, with visual stimuli, some degree of spatial specificity ( Fulcher et al, 2016 ; see also Johnston et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting question is whether distortions of visual time induced by motor adaptation are the consequence of a change in the activity of a specific associative area (like Intraparietal Sculcus) or the result of a change in temporal processing inherited along multiple levels of the visual hierarchy (Webster, 2011(Webster, , 2015. For example, Heron, Fulcher, Collins, Whitaker, and Roach (2019) have recently demonstrated that adaptation-induced changes in duration estimates spread along several stages in the visual processing hierarchy. In particular, they reported that duration encoding mechanisms at monocular, depth-selective, and depth-invariant stages all play a distinct role in defining duration aftereffects.…”
Section: A B C Dmentioning
confidence: 99%
“…First, there is evidence supporting the existence of numerosity-selective ''channels'' or groups of neurons tuned to a preferred numerosity (Harvey & Dumoulin, 2017;Harvey, Fracasso, Petridou, & Dumoulin, 2015;Harvey, Klein, Petridou, & Dumoulin, 2013;Kutter, Bostroem, Elger, Mormann, & Nieder, 2018;Piazza, Izard, Pinel, Le Bihan, & Dehaene, 2004). Likewise, there is evidence suggesting that there are duration-selective channels tuned to a preferred duration that are dedicated to processing specific temporal features (Hayashi et al, 2015;Heron et al, 2012;Heron, Fulcher, Collins, Whitaker, & Roach, 2019;Ivry, 1996;Motala, Heron, McGraw, Roach, & Whitaker, 2018;Protopapa et al, 2019;Walker, Irion, & Gordon, 1981). The duration channels revealed using adaptation appear to encode the interval between the onset and offset duration of an event (Heron et al, 2012;Maarseveen, Paffen, Verstraten, & Hogendoorn, 2019), a finding which is further supported by neurophysiological studies in animals (Duysens, Schaafsma, & Orban, 1996;Ehrlich, Casseday, & Covey, 1997;He, Hashikawa, Ojima, & Kinouchi, 1997).…”
Section: Introductionmentioning
confidence: 99%